Practicing Communicability, Redeemability, and Educability: The Response of Christian Education to Violence against Women during the Covid-19 Pandemic - Jeniffer Fresy Porielly Wowor (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
This article explores violence against women in Yogyakarta, which increased rapidly during the pandemic. The study showed that violence against women is also the result of deep and troubling cultural structures that oppress women. Based on a see–judge–act analysis, this article proposes that church educational ministries can build relationships with women victims and their families through a variety of transformational ways, even amid a pandemic. The church can develop communication, healing, and education through a holistic approach in Christian education (practicing communicability, redeemability, and educability). The paradigm of gender equality should be integrated into our attitudes and actions in daily life and in the whole range of the church’s ministry to create spaces for women’s voices not only through education and ritual action but also actual transformation.